1978
DOI: 10.1021/bi00616a031
|View full text |Cite
|
Sign up to set email alerts
|

Structural limitations on the bifunctional intercalation of diacridines into DNA

Abstract: An homologous series of diacridines containing two 9-aminoacridine chromophores linked via a simple methylene chain has been studied in order to investigate the minimum interchromophore separation required to permit bifunctional intercalation. Viscometric, sedimentation, and electric dichroism experiments show that compounds having one to four methylene groups in the linker are restricted to monofunctional intercalation, whereas the interaction becomes bifunctional when the chain length is increased to six car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
102
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 15 publications
8
102
0
Order By: Relevance
“…The first evidence suggesting violation of the neighborexclusion model was obtained from viscometric studies (12)(13)(14) on interactions between bi-and triderivatives of acridine and DNA, where it was suggested that a single base pair was sandwiched between two acridines. 1H NMR studies on the binding of a series of bis(acridine) compounds to d(AT)5d(AT)5, in which the two acridine rings were linked through linker chains of various lengths, found no evidence of violation of the neighbor-exclusion principle (15,16).…”
mentioning
confidence: 99%
“…The first evidence suggesting violation of the neighborexclusion model was obtained from viscometric studies (12)(13)(14) on interactions between bi-and triderivatives of acridine and DNA, where it was suggested that a single base pair was sandwiched between two acridines. 1H NMR studies on the binding of a series of bis(acridine) compounds to d(AT)5d(AT)5, in which the two acridine rings were linked through linker chains of various lengths, found no evidence of violation of the neighbor-exclusion principle (15,16).…”
mentioning
confidence: 99%
“…This is in stark contrast to the analogous diacridine series in which bisintercalation is found for the C6 and higher homologues [19]. Indeed, the actual values of the unwinding and extension parameters suggest that the C2 and C7 diquinolines intercalate monofunctionally, whereas the other derivatives are poor intercalators and interact with a fair proportion bound wholly externally.…”
Section: Discussionmentioning
confidence: 67%
“…The viscometric technique is well established as a method for investigating the extension of the DNA helix associated with intercalation [15][16][17][18]. Under conditions where the DNA molecules behave as stiff rods:…”
Section: Methodsmentioning
confidence: 99%
“…This gives the helix extension ratio L/L o = 1 + 2r for monofunctional intercalation and L/L o = 1 + 4r for bifunctional intercalation [ 18], where r represents the binding ratio Effect of eehinomycin on the relative contour length of (a) poly(dA-dT) and (b) poly(dG-dC). The ordinate represents the fractional increase in helix length; the abscissa shows the binding ratio (r), drug molecules bound/nucleotide, calculated from the input ratio (DIP) using the binding parameters in [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation